2023
DOI: 10.1002/mde.3782
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and competition with human capital input

Abstract: As innovation relies on human capital heavily, it attaches importance to taking human capital into account while investigating the relationship between innovation and competition. This paper establishes a game theory model to capture the effects of competition on innovation with human capital. The major findings indicate that firms with larger scale are more active in innovation investment. Meanwhile, a lessening of competition is beneficial to increase innovation if human capital input is considered.Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Game theory, a mathematical tool used to analyze strategic interactions among rational decision-makers, is particularly relevant in understanding the complexities of human capital export (Bossaerts and Murawski, 2017;Pandey, and Chermack, 2008;Nie et al 2023). Our study applies game-theoretic principles to model the decisions faced by potential human capital exports (individuals considering migration for employment) and receiving countries.…”
Section: Methodsmentioning
confidence: 99%
“…Game theory, a mathematical tool used to analyze strategic interactions among rational decision-makers, is particularly relevant in understanding the complexities of human capital export (Bossaerts and Murawski, 2017;Pandey, and Chermack, 2008;Nie et al 2023). Our study applies game-theoretic principles to model the decisions faced by potential human capital exports (individuals considering migration for employment) and receiving countries.…”
Section: Methodsmentioning
confidence: 99%
“…Other empirical studies confirmed the unidirectional causality from economic growth to innovation (Cetin, 2013;Howells, 2005;Pradhan et al, 2018;Sadraoui et al, 2014). Nie and Yang (2023) argued that innovation heavily depends on human capital and stressed the importance of considering this factor when examining the relationship between innovation and competition. Human capital has long been recognized as crucial in fostering innovation at the country and firm levels.…”
Section: Introductionmentioning
confidence: 90%
“…Nie and Yang (2023) argued that innovation heavily depends on human capital and stressed the importance of considering this factor when examining the relationship between innovation and competition. Human capital has long been recognized as crucial in fostering innovation at the country and firm levels.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al (2023b) [ 32 ]found that the incentive effect of tax incentives on ESG performance of enterprises is more significant in state-owned enterprises, enterprises in the eastern region, larger enterprises, enterprises with more concentrated equity, and enterprises with better internal control quality. Furthermore, Nie and Yang (2023) [ 33 ]pointed out that the larger the enterprise, the more active innovation investment becomes. Therefore, it remains to be further explored the exact effect of environmental taxes on specific firms in China.…”
Section: Literature Reviewmentioning
confidence: 99%